Family-Centered Approach to Malnutrition Management: A Case Study in Cikupa, Indonesia - Renaldy; Ernawati (Open Access Indonesian Journal of Medical Reviews, 2024)
Malnutrition remains a significant public health issue globally, particularly in developing countries like Indonesia. This case report describes the successful management of malnutrition in a 1-year-old child using a family-centered approach within the framework of family medicine principles. A 1-year-old male child presented to the Cikupa Health Center with a history of poor weight gain and recurrent infections. A comprehensive assessment using the Mandala health assessment revealed multiple contributing factors, including suboptimal breastfeeding practices, inadequate complementary feeding, poor environmental sanitation, and limited parental knowledge of nutrition and hygiene. A tailored management plan was implemented, encompassing nutritional interventions, deworming medication, education on hygiene and sanitation, and family support. The child showed positive outcomes, including improved weight gain, reduced frequency of infections, and enhanced growth and development trajectory. In conclusion, this case highlights the effectiveness of a family-centered approach in managing malnutrition. By addressing the interconnected biological, psychological, social, and environmental factors, healthcare providers can achieve sustainable improvements in child health and well-being.